Inquiry-Based Learning Implementation In English Teaching For Sixth Grade Students At SDN 016 Samarinda Seberang - Wahyuni Putri; Dyah Sunggingwati; Desy Rusmawaty (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2021)
Inquiry-Based Learning (IBL) was defined as a learning model to develop students’ understanding of language content and scientific practices. In K13 curriculum, it was also considered as one of the learning models recommended by the government to be applied in the teaching and learning process. This study focused on the IBL implementation in English teaching for sixth-grade students at SDN 016 Samarinda Seberang. The purposes of this study were: (1) to know how IBL is implemented in English teaching; (2) to know the problems faced by the teacher during the implementation of IBL method in English teaching. This research used descriptive qualitative research. The subject was an English teacher from SDN 016 Samarinda Seberang. The data were collected from observation sheet notes and interviews. The data classified according to the identified problems and were analyzed by using the descriptive analysis method. The findings showed that the teacher used six IBL procedures such as (1) stimulation (2) problem statement (3) data collection (4) data processing (5) verification (6) generalization. Also, the subject appropriately applied videos and pictures to deliver the material. During its implementation, technological problems (i.e: unstable connection, delay, display error) and pedagogical problems (i.e: time consuming in preparing a lesson plan, need to provide a lot of stimulation media, and unable to conduct collaborative work) occurred in online classroom. It was suggested for the teacher to keep practicing on IBL in the teaching process, be more patient in creating creative activities, participate in teaching workshop, and discuss the lesson plan with other English teachers. Meanwhile, for the next researcher, it is suggested to explore IBL in other skills or other levels of students since the current study only focused on the implementation of IBL for sixth grade students.